Effect of fluid on wave propagation in weakly anisotropic porous media - Collet, O.; Gurevich, Boris (American Society of Civil Engineers, 2013)
Predicting seismic velocities in isotropic fluid-saturated rocks is commonly done using the isotropic Biot-Gassmann theory. For anisotropic media, the Biot-Gassmann solution is expressed in terms of stiffness or compliance, which does not provide an intuitive understanding on the impact of fluid on anisotropy. To analyse how the pore fluid affects wave propagation in weakly anisotropic media, we rederived these expressions in terms of dimensionless anisotropy parameters. Besides, we study the effect of fluid on two anisotropy patterns, the one caused by aligned fractures embedded in an isotropic porous background and the stress-induced anisotropy pattern. By deriving an approximation of the anellipticity parameter η, we show that if the dry medium is elliptical, the saturated medium is also elliptical but only if the porosity is not too small. This result can provide a way of differentiating between stress- and fracture-induced anisotropy.